Investigating of the doctor's speech within the framework of pragmalinguistics (Texas Journal of Philology, Culture and History, 2023)
Following article deals with the term of pragmalinguistics and the methodology of its study. Pragmatics and its entry into linguistics as a separate branch of linguistics have been discussed in detail in the article. Communicative linguistics, the study of speech activity and actions as a language have been analyzed as well. The principles of differentiation between pragmalinguistics and hidden pragmatics have been revealed in the article. Examples of hidden pragmalinguistics are given in the doctor's speech. Actually, this direction is used together with direct speech-communication terms and explained with examples. Without them, it is difficult for pragmalinguistics to reveal its potential. The article highlights the fact that pragmalinguistics is directly studied as a quality of semiotics and introduced as a separate direction. It was mentioned in our study that speech etiquette is the main tool of pragmalinguistics. In the article, speech etiquette, speechcommunication, subject-addressee and pragmalinguistics were interpreted as the object of study of our direct research.